2017
DOI: 10.1186/s40066-017-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations of household food insecurity in East Gojjam Zone, Amhara Region, Ethiopia: implications for agroecosystem-based interventions

Abstract: Background: In Ethiopia, food insecurity remains a major public health challenge. Agroecosystem has a potential to determine food insecurity. Therefore, this study aimed to determine the spatial pattern of household food insecurity across different agroecosystems in East Gojjam Zone. An agroecosystem-linked cross-sectional survey was done among 3108 households after selecting using multistage cluster sampling. The study area is divided into hilly and mountainous highlands, midland plains with black soil, midla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
(54 reference statements)
4
16
1
Order By: Relevance
“…The current figure was higher than the previous study report from other studies in Ethiopia, including Addis Ababa 75% [31], Tigrai 68.8% [32], Amhara 65.3% [33], Afar 70.4% [34], Oromia 58.5 % [35], and Gojjam, Amhara 58.1% [36]. Comparatively, study reports from other countries such as South Eastern Kenya 62.7% [37] and Latin America 75% and 25%, reported moderate to severe food insecurity [38].…”
Section: Discussioncontrasting
confidence: 75%
“…The current figure was higher than the previous study report from other studies in Ethiopia, including Addis Ababa 75% [31], Tigrai 68.8% [32], Amhara 65.3% [33], Afar 70.4% [34], Oromia 58.5 % [35], and Gojjam, Amhara 58.1% [36]. Comparatively, study reports from other countries such as South Eastern Kenya 62.7% [37] and Latin America 75% and 25%, reported moderate to severe food insecurity [38].…”
Section: Discussioncontrasting
confidence: 75%
“…Our study indicates that MDD among children at national and regional levels are non-random (Moran's I: 0.18 and 0.48, 0.01) in 2011 and 2016 datasets respectively, which is consistent with prior research. [30][31][32] Further, the result of regression analysis indicated that the observed variation in DD among children in Ethiopia is attributed to both individual and community-level factors. The finding of both spatial and regression analysis over the past two surveys identified high-risk regions consistently.…”
Section: Discussionmentioning
confidence: 96%
“…This dilemma warrants targeted strategies to first identify food-vulnerable geographical locations, so as to inform prioritized interventions for the most affected areas (which may have mental health implications, yet to be examined). With some exceptions from Nigeria 25 and Ethiopia 26 , there are few recent national-level studies from sub-Saharan African (SSA) countries 27 on the spatial variability of household food insecurity. In this current study, we will use of novel spatial statistical methods to first identify geographical clusters (“hotpots”) of food insecurity, and assess its association with depression, based on panel data from the South African National Income Dynamics Study (SA-NIDS), a unique nationally-representative sample of South Africans, with geographical coordinates for each household.…”
Section: Introductionmentioning
confidence: 99%